Phytochemical analysis and antioxidant properties of keladi candik (Alocasia longiloba) plant - Hemalatha Gengaderan (2016)
Alocasia longiloba is one of the medicinal plants in Asia which is underutilized due to lack of knowledge available about it. Alocasia plants having many medicinal uses like external wound treating property, anti-toxic reputation, anti-bacterial properties and ect. The aim of this study are to determine the total phenolic and flavonoid contents and antioxidant property of A. longiloba plant extracts besides to identify the bioactive compounds in A. longiloba plant extracts showing the activity using GC/MS. In this study, leaf and petiole extracts of the plant prepared in different polarity solvents which are 95% ethanol, 50% ethanol, water and hexane by using Soxhlet extraction method. Total phenolic content and total flavonoid content were determined by using Colorimetric and Folin-reagent methods respectively. Antioxidant potential was determined using DPPH radical scavenging assay method and ABTS assay method. Finally, GC/MS analysis was done to identify the active compounds present in the plant extracts that shown the activity.